2014
DOI: 10.1111/jth.12627
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of venous thromboembolism in commercial airline pilots: a cohort study of 2630 pilots

Abstract: Summary. Background: Airline pilots may be at increased risk of venous thromboembolism (VTE) because air travel has recently been established as a risk factor for VTE. Objectives: The aim of this study was to assess the risk of VTE in a cohort of Dutch airline pilots. Patients/Methods: Airline pilots who had been active members of the Dutch aviation society (VNV) were questioned for the occurrence of VTE, presence of risk factors for VTE and number of flight hours per year and rank. Incidence rates among pilot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“… 16 , 17 In the previous studies, we selected controls from patients presenting to coronary care unit, based on the landmark case-control study on traveller’s thrombosis 8 and recognition of common risk factors for venous thromboembolism and atherosclerosis. 17 , 18 We hypothesised that this coronary care unit group might result in an underestimation of the risk associated with prolonged seated immobility as such patients may be more likely to have a sedentary occupation due to limitations placed on them by their cardiovascular disease. For this reason, we chose a different control group, a ‘healthy’ group presenting to the Emergency Department with upper limb injury in whom there was no clinical suspicion of venous thromboembolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 16 , 17 In the previous studies, we selected controls from patients presenting to coronary care unit, based on the landmark case-control study on traveller’s thrombosis 8 and recognition of common risk factors for venous thromboembolism and atherosclerosis. 17 , 18 We hypothesised that this coronary care unit group might result in an underestimation of the risk associated with prolonged seated immobility as such patients may be more likely to have a sedentary occupation due to limitations placed on them by their cardiovascular disease. For this reason, we chose a different control group, a ‘healthy’ group presenting to the Emergency Department with upper limb injury in whom there was no clinical suspicion of venous thromboembolism.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible the selection of controls derived from coronary care unit may be preferable, on the basis that it may be more representative of the population at risk of presentation to hospital with a venous thrombosis. 17 , 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 However, two well-conducted studies in captive populations have shown that the absolute IR of VTE does not seem to differ from that in general population. 17,18 Nevertheless, there is a possibility that immigrants might have developed VTE events during this period that would not have been captured, but because of the aforementioned reasons we believe that it is unlikely that a significant number of events were missed. In any case such limitation would apply to all immigrant groups and it would have very little effect on the risk ratios.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, although long‐distance travel has been reported to slightly increase the risk of VTE such risk is difficult to measure due to the lack of proper follow‐up in travelers 16. However, two well‐conducted studies in captive populations have shown that the absolute IR of VTE does not seem to differ from that in general population 17, 18. Nevertheless, there is a possibility that immigrants might have developed VTE events during this period that would not have been captured, but because of the aforementioned reasons we believe that it is unlikely that a significant number of events were missed.…”
Section: Discussionmentioning
confidence: 99%